Analysis of Malaysian mortality rates by specific ethnics, age groups and gender before and during Covid-19 pandemic - Nurainina Zakiah Hamzah; Rose Irnawaty Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia has been one of the Western Pacific region's nations that has been adversely affected by the COVID-19 pandemic with over 32,000 deaths linked to COVID-19 over three major epidemic waves, and a cumulative case count of over six hundred million worldwide. The study aims to investigate the trend of mortality rates for the three major ethnic groups in Malaysia, which are Bumiputera, Chinese, and Indians for the age groups of adults, middle age, and elderly for both genders. Since data on mortality rates in Malaysia is only accessible for age groups such as 1–4, 5–9, 10–14, 15–19, and so on, a distributional or interpolation approach was required to expand it to the individual ages. Thus, the Lagrangian interpolation is used to estimate the values of mortality for each individual age. The study also intends to identify which ethnic, age groups and gender that were most affected during the pandemic. Overall, it was found that the trend is decreasing for all age groups and gender for years before the pandemic. The ethnic group that most affected during the pandemic was Chinese females aged 24 to 39 with a 13.89 percent increment in 2021. However, there are some deviations from the pattern observed during the COVID-19 pandemic. Also, mortality rates for females are consistently lower than males across all age groups. Surprisingly, for the elderly, mortality rates are consistently lower, even during the pandemic for both males and females. This happened due to the ageing population process whereby the proportion of the elderly increased significantly as Malaysia is expecting to be an ageing population country by year 2030.